2022
DOI: 10.1186/s12887-022-03350-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of childhood obesity and related genetic factors on precocious puberty: protocol for a multi-center prospective cohort study

Abstract: Background Childhood obesity has important effects on the onset and development of puberty. Although a number of studies have confirmed the relationship between obesity and precocious puberty, little is known about the pleiotropic genes of obesity and precocious puberty and the interaction between genes and environment. There are four objectives: (1) to analyze the incidence of precocious puberty in the general population in China; (2) to verify the direct effect of obesity on children’s precoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…Another mechanism may be through the development of adiposity. Our study found that the obesity rate of the case group was higher than that of the control group, which reflected that obesity was a risk factor for precocious puberty and consistent with the previous research findings [ 37 – 39 ]. Childhood obesity is associated with early menarche [ 40 ], and the intake of some food (including hamburgers and hot dogs) in the red meat group was associated with children being overweight in this population [ 41 ].…”
Section: Discussionsupporting
confidence: 92%
“…Another mechanism may be through the development of adiposity. Our study found that the obesity rate of the case group was higher than that of the control group, which reflected that obesity was a risk factor for precocious puberty and consistent with the previous research findings [ 37 – 39 ]. Childhood obesity is associated with early menarche [ 40 ], and the intake of some food (including hamburgers and hot dogs) in the red meat group was associated with children being overweight in this population [ 41 ].…”
Section: Discussionsupporting
confidence: 92%
“…Previous epidemiological studies and genetic evidence have consistently indicated a causal association between obesity in girls and earlier puberty onset [ 7 , 8 , 10 , 42 , 43 , 44 ]. Our study confirmed that childhood obesity and increased BMI contributed to a younger age of menarche and increased Tanner stage in girls, offering further support for these conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…In the suspicion of early sexual maturation, in kids presenting signs of secondary sexual development before the age of eight (females) or nin (males), the evaluation should begin with an accurate medical and familial history as shown in Figure 1 [22,34]. It is important to collect information regarding age of onset, rate of maturation of secondary sexual characteristics, exposure to exogenous sex steroids and the presence of neurological symptoms [10,14].…”
Section: Diagnosismentioning
confidence: 99%